LOKALITAS KERAMIK (KESINAMBUNGAN ESTETIKA DAN BUDAYA) - Yustana, Prima (Institut Seni Indoensia Surakarta, 2016)
This study aimed to examine the characteristics of ceramic products produced by artisans in Indonesia that documented in the literature references. The problems that are very interesting to know is whether there is continuity of the history of the development of the existing ceramic Indonesian territory or people also often refer archipelago. Indonesia has a lot of existing areas, each location thereis a life that determines the development of ceramics, various characteristics of ceramic products both artifacts and decorative and beauty has the sole purpose different. Under these conditions, the sustainability of these developments are worth mentioning as ceramic locality. Analysis of literature is needed to support the argument accuracy in analyzing a problem, various approaches by using areference would be very supportive in this study, this study will be very interesting when it first tried to find out the origin of both the craft center through the historical approach, the accuracy of the data into better to use as a literature review of relevant literature artifacts through to dissect the artifacts.Multidisciplinary be a force in this literature-based research especially by taking samples directly image and any information contained in the relevant literature. This research method will use qualitative research methods that are supported by the data the theory according to some experts who have done research and the information is written in the book. Targeted research is to identify and analyze scientifically how the actual local forces or the values of existing locality on the archipelago so as to address challenges both nationally and globally about the identity of the ceramic archipelago. Through a multidisciplinary approach will provide greater insight from various angles both the beauty, culture and history so that if this research can produce a reference book, it can be used as a reference for both students and students to strengthen national identity as a means of responding to global challenges as well as guidance on how the importance of locality in each nation’s childrenKeywords: Locality, Ceramics, Aesthetics and Culture.